Photocatalytic water splitting - Kuo, Yenting (Kansas State University, 2011)
New photocatalystic materials Ti-In oxy(nitride) and nanosized Ru-loaded strontium titanate doped with Rh (Ru/SrTiO3:Rh) have been synthesized. The textural and surface characteristic properties were studied by nitrogen BET analysis, diffuse reflectance UV-vis spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy, scanning electron microscopy and powder XRD. The photocatalytic properties were enhanced by the binary metal oxides of titanium dioxide and indium oxide. The XRD patterns confirmed the oxygen exchange between two metal oxides during the synthesis. Moreover, the presence of titanium dioxide can help the stabilization of InN during hot NH3(g) treatment. On the other hand, the particle sizes of aerogel prepared Ru/SrTiO3:Rh varied from 12 to 25 nm depended on different Rh doping. A mixture of ethanol and toluene was found to be the best binary solvent for supercritical drying, which yielded a SrTiO3 sample with a surface area of 130 m2 Enhanced photocatalytic hydrogen production under UV-vis light irradiation was achieved by ammonolysis of intimately mixed titanium dioxide and indium oxide at high temperatures. Gas chromatography monitored steadily the formation of hydrogen when sacrificial (methanol or ethanol) were present. XRD patterns confirmed that the photocatalysts maintain crystalline integrity before and after water splitting experiments. Moreover, the presence of InN may be crucial for the increase of hydrogen production activities. /g and an average crystallite size of 6 nm. These Ru/SrTiO3:Rh photocatalysts have been studied for photocatalytic hydrogen production under visible light. The band gap of the bulk SrTiO3 (3.2 eV) does not allow response to visible light. However, after doping with rhodium and loaded with ruthenium, the modified strontium titanates can utilize light above 400 nm due to the formation of valence band or electron donor levels inside of the band gap. Moreover, the surface areas of these photocatalysts are much larger than conventional solid-state synthesized samples (1-2 m 2/g), which yielded more Ru loading and reaction sites. The areogel and hydrothermal synthesized samples required basic (alkaline) conditions for hydrogen generation facilitation compared with acidic conditions for conventional solid-state samples.
Keywords: water splitting; renewable energy; Chemistry (0485)